The Implementation of Defense Development Policy in Indonesia – Timor Leste Territorial Border (A Case Study at Belu Regency Nusa Tenggara Timur Province) - Rahman, Mulyawan (British Journal of Multidisciplinary and Advanced Studies, 2022)
This study discuss the Implementation of Defence Sector Development Policy at the Indonesia’s Border Region – Timor Leste (Case Studies in Belu Regency of East Nusa Tenggara Province). The study was conducted due to curent development in the field of defence affairs as the authority of the central government but in its implementation still has weakness in maintaining national sovereignty and stability. The study used the case study method, which is part of qualitative research. Data collection techniques were done by exploring the data derived from primary and secondary sources. Primary data in the form of words, speech and action or behavior gathered from 15 informants, as well as secondary data obtained from various documents, journals, scientific papers, and others. The results suggested that the policy implementation model proposed by Cheema and Rondinelli has been implemented by the Belu District. However, the model was not appropriate to be applied in the border region because the model does not prioritize coordination aspect. Researcher argues that the implementation of Cheema and Rondinelli’s could have been more successful if it was equipped with the coordination aspect. This coordination aspect becomes important because there are many institution in Belu District that are competent in the sucessful execution of defence development policy.